A comparison of methods for measuring the induction time for bubble–particle attachment. (September 2015) - Verrelli, David I.; Albijanic, Boris
Graphical abstract: Highlights: Critical review of techniques for measuring the induction period for attachment. Comparison of induction time estimates using different experimental techniques. Matching conditions within different measurement devices may allow calibration. Cross-calibration of different techniques boosts robustness and permits comparison. Correct statistical approach to estimate confidence interval of binomial variable. Abstract: Froth flotation is an exceedingly complex physicochemical process. The convenience of distilling much of the complexity of the particle–bubble interactions into a single parameter has led to the continuing popularity of the classical 'induction time' to quantify the threshold for particle–bubble attachment to occur. Despite this popularity and the simplicity of the concept, there is no single universal method of evaluating the induction period. In this paper, we begin with a critical review of the available techniques for estimating the induction period. These are: back-calculation from experimental (micro)flotation tests; pushing a particle toward a stationary bubble (or vice versa ) using an atomic force microscope (AFM); pushing a bubble toward a stationary bed of particles in the ' Induction Timer '; pushing a bubble toward a stationary solid surface using the 'integrated thin film drainage apparatus' (ITFDA); and dropping particles onto a submerged stationary bubble using the ' Milli-Timer ' device. Each one of these methods has advantages and disadvantages, and the best choice depends on the application. In the experimental section, we present quantitative comparison of the induction periods estimated using two different techniques, namely the Induction Timer and the Milli-Timer . The same particles were tested in each device, under the same conditions. It was found that by tuning the operation of the particle pick-up device, similar estimates of induction period could be obtained to the estimates made by direct observation with the Milli-Timer . In the former device a bubble is driven toward a particle bed at a controlled rate, whereas in the latter a particle's motion is governed by the hydrodynamics. The potential to match these presents an intriguing prospect for better understanding the bubble–particle interaction, and the possibility to 'calibrate' the simpler Induction Timer against direct observations.